DIRECTIVE ILLOCUTIONARY ACT PRODUCE BY THE CHARACTERS IN CRUELLA MOVIE - FEBRIOLA, NIA FEBRIOLA (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The aims of this study are to find out the types of directive act and its function that is found in American Disney movie entitled Cruella which released in 2021. The study conducted with observation method and analyzed using quantitative and qualitative methods. The researcher collect the data through several steps, such as watching the movie several times, taking note the utterance indicated as directive act and classifying the utterance into the types of directive. The theory proposed by Searle (1979) was applied in order to analyze the data. Therefore, the result of this study found there are 51 utterances consider as directive act. The data divided into five types including ask (16), suggest (10), forbid (7), order (9) and request (3). From the total data, asking become the most frequencies found in the movie since the character frequently used the question to get the hearer give an answer or the information. It followed by the occurrence of suggest on the second rank of total data found. The speaker produces the type of suggestion in order to suggest the hearer in doing an action.